DAMPAK FAKTOR INTERNAL PERUSAHAAN TERHADAP FIRM VALUE DENGAN PEMODERASI FIRM SIZE PADA PERUSAHAAN INDUSTRI ENERGI DI INDONESIA DAN MALAYSIA - Prasetyo, Aries Heru; Rusli, Yohanes Mardinata (Universitas Pelita Harapan, 2024)
Increasing the company's value is the main goal of the company, namely by increasing the stock price. High stock prices will make the market believe in the company's performance and its prospects in the future. The company's financial managers are expected to be able to understand the factors that affect the company's value in order to increase the company's value and prosper shareholders. This study aims to determine the effect of capital structure, company size, and company growth on the value of energy companies listed on the Indonesia Stock Exchange (IDX) and Bursa Malaysia (BM) during the period 2019 to 2021. Sampling was selected using the purposive sampling method and the data analysis method used was panel data regression analysis using the EVIEWS 10 program to process the data. Based on the results of the panel data regression analysis of this study, the results of this study are as follows: (i) Capital Structure has a positive and significant effect on Firm Value in energy industry companies on the IDX; (ii) Company Growth does not have a significant effect on Firm Value in energy industry companies on the IDX; (iii) Firm Size strengthens the influence of Capital Structure on Firm Value in energy industry companies on the IDX; (iv) Firm Size does not moderate the influence of Company Growth on Firm Value in energy industry companies on the IDX; (v) Capital Structure has a positive and significant influence on Firm Value in energy industry companies on the BM; (vi) Company Growth has a positive and significant influence on Firm Value in energy industry companies on the BM; (vii) Firm Size strengthens the influence of Capital Structure on Firm Value in energy industry companies on the BM; (viii) Firm Size does not moderate the influence of Company Growth on Firm Value in energy industry companies on the BM; This study only tests energy industry companies in the capital market of Indonesia and the capital market in Malaysia, it is suggested that further research can also test other industrial companies and also in the capital markets of Asian countries other than Indonesia and Malaysia.